Interactive media on bathroom appliances - 396734 Ng, Shin Tee (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Mechanical Engineering (Industrial Science)) - Universiti Teknologi Malaysia, 2004